Reconstructing the Integrative Paradigm of Islamic Education: A Critical Analysis of Integrated Islamic Schools in Indonesia: Merekonstruksi Paradigma Integratif Pendidikan Islam: Analisis Kritis terhadap Sekolah Islam Terpadu di Indonesia - Qiso, Ahamad A.; Ani Nafisah; Erik Pebrikarlepi; Muhammad Wahyudi; Ferry Heryadi (Al-Ishlah: Jurnal Pendidikan Islam, 2025)
The persistent dichotomy between religious and secular knowledge remains a critical issue in Islamic education in Indonesia. Integrated Islamic Schools (SIT) emerged as an alternative solution to bridge this divide by offering a holistic educational model. However, in practice, their integrative efforts often remain superficial, symbolic, and lack epistemological coherence. This study aims to critically reconstruct the paradigm of knowledge integration in SIT by employing library research and content analysis of foundational works by key Islamic scholars such as Ismail Raji al-Faruqi, Syed Muhammad Naquib al-Attas, and M. Amin Abdullah. The findings indicate that SIT’s integration model lacks a conceptual framework grounded in Islamic epistemology, fails to develop context-based Islamic science, and predominantly relies on ritualistic practices without substantive engagement. To address these gaps, the study introduces the Tauhidic Paradigm, consisting of three pillars: tauhid as an epistemological foundation, adab and ethics as educational orientation, and knowledge interconnectivity as a contextual pedagogical strategy. This paradigm contributes theoretically to Islamic educational discourse by offering a coherent epistemological model and practically by informing curriculum reform and pedagogical practices in SIT. Unlike previous descriptive studies, this article offers a critical and reconstructive approach that